Parenting Styles of Teen Mothers in a Selected City in Mindanao, Philippines - Leila D. Benito (Randwick International of Social Science Journal, 2022)
The study explored the parenting styles of teen mothers in a particular city in Mindanao, Philippines. It used a descriptive cross-sectional quantitative approach specifically a survey to gather the needed data among 377 teen mothers who were chosen based on stratified random sampling. Findings revealed that parenting styles are authoritative followed by permissive, and lastly, authoritarian. Variables involved were age, civil status, family structure, ethnicity, educational attainment, and age of menarche. Moreover, using multiple regression, findings revealed that age, civil status, family structure, ethnicity, educational attainment, and age of menarche are not predictors for the parenting styles of the teen mother participants of the study.